Scanning and three-dimensional-printing using computed tomography of the “Golden Boy” mummy - Saleem, Sahar N.; Seddik, Sabah Abd el-Razek; el-Halwagy, Mahmoud (Frontiers in Medicine, 2023)
Ancient Egyptian mummies represent an opportunity to learn more about the health, beliefs, and skills of humans in antiquity. A fully wrapped mummy, from a Late Ptolemaic cemetery (c.332-30 BC) in Edfu, Egypt, has been stored, unexamined, at the Cairo Egyptian Museum since 1916. We hypothesized that scanning and 3D-printing the mummy using Computed Tomography (CT) could help in documenting and promoting its public display. CT enabled non-invasive digital unwrapping and revealed a well-preserved mummy. Biological sex could be determined from the presence of male genitalia; epiphyseal fusion and tooth eruption indicated an approximate age at death of 14–15 years. The deceased had healthy teeth and bones without evidence of poor nutrition or disease. CT detected a high-quality mummification process that included brain removal through an iatrogenic defect of the cribriform plate and viscera removal via a left lower-abdominal incision. The heart remained in the chest as a spiritual symbol. Resin was poured into the emptied cranial and torso cavities, and linen packs were placed inside the torso. The Mummy’s external ornamentation includes a gilded head mask, a pectoral cartonnage, and a pair of sandals. CT identified 49 amulets inside the mummy and between the wrappings, arranged in three columns. The amulets have 21 different shapes, including Udjat, scarabs, Ajet, Djed-pillar, Tyt, Placenta, Double-Plume, and Right-angle. CT densities indicated that 30 (61%) amulets were metal (likely gold), and the other amulets were made of faience, stones, or fired clay. The embalmers placed amulets to protect and provide vitality for the body for the afterlife. A gold tongue amulet was placed inside the mouth to ensure the deceased could speak in the afterlife. A Two-finger amulet was placed beside the penis to protect the embalming incision. 3D-printing enabled the tactile and visual study of a heart scarab found inside the thoracic cavity. Findings from this study suggest that ancient Egyptians valued their children and provided them with ritual treatment. State-of-the-art techniques such as CT and 3D printing provided valuable insights and supported the museum display of the mummy, nicknamed “The Golden Boy.”